Nonlinear composite beam theory - Hodges, Dewey H. (American Institute of Aeronautics and Astronautics, 2006)
Beginning with an overview of the theory developed over the last 60 years, Dr. Hodges addresses the kinematics of beam deformation, provides a simple way to characterize strain in an initially curved and twisted beam, and offers cross-sectional analysis for beams with arbitrary cross sections and composed of arbitrary materials. He goes on to present a way to accurately recover all components of cross-sectional strain and stress before providing a natural one-dimensional (1-D) theory of beams. Sample results for both cross-sectional and 1-D analysis are presented as is a parallel treatment for thin-walled beams.
Keywords: Composite construction.; Girders -- Mathematical models.; Girders.; elektronické knihy; electronic books